The reaction of the circulatory system to stress and electromagnetic fields emitted by mobile phones - 24-h monitoring of ECG and blood pressure - Agata Szyjkowska; Elzbieta Gadzicka; Wiesław Szymczak; Alicja Bortkiewicz (Nofer Institute of Occupational Medicine, 2019)
Background Experimental studies have shown cardiovascular effects of electromagnetic fields (EMF) emitted by mobile phones (e.g., prolonged QTc interval and abnormal blood pressure [BP] values). Also, stress may have an impact on the cardiovascular function. However, there are practically no data regarding the joint effect of exposure to stress and EMF, with both factors pertaining, e.g., to employees of mobile network operators. Material and Methods Out of 208 subjects who had taken part in survey research, 55 workers agreed to undergo resting ECG, 24-h ECG and ambulatory blood pressure monitoring (ABPM). Their health condition, occupational and life-stress levels and EMF exposure were also assessed. Results Among the workers using mobile phones for more than 60 min daily, the systolic BP values in office measurement and at night-time in ABPM were significantly higher than among the workers spending less time talking on mobile phones (p = 0.04 and p = 0.036, respectively). The workers with the highest level of occupational stress showed significantly higher systolic 24-h BP (p = 0.007) and at day-time (p = 0.002), both during work (p = 0.010) and after work (p = 0.005), and higher diastolic BP values at day-time (p = 0.028). Cardiovascular response was strongly gender-related: males showed more BP abnormalities while females displayed more impairments in ECG records. The heart rate from 24 h was significantly correlated with the level of occupational stress, after adjusting for gender, life-stress and EMF. Conclusions The findings obtained thus far have indicated the need to conduct in-depth studies on the impact of stress and EMF emitted by mobile phones on the health effects, in order to clarify the observed gender-related differences in cardiovascular response to the combined exposure to stress and EMF. Med Pr. 2019;70(4):411-24